An interesting sexually dimorphic species, Chamobates callipygis Pavlichenko, 1991 (Acari, Oribatida, Chamobatidae), with remarks on sexual dimorphism in Ceratozetoidea - Bayartogtokh, Badamdorj; Ermilov, Sergey G.; Khaustov, Alexander A. (Zootaxa, 2022)
Based on materials from the leaf litter of a mixed forest in Crimea, a new diagnosis for the sexually dimorphic species, Chamobates callipygis Pavlichenko, 1991, is presented to accommodate its previously unreported females. This is the only species in Chamobatidae showing a distinct sexual dimorphism, which is expressed by the posterior porose region on the notogaster, such that males only have a large protuberance on the posterior part of notogaster bearing a pair of fused porose areas A3, and a densely striated region behind them. The specific function of this structure is not yet known, but the sexual dimorphism is presumably involved in pheromonal communication facilitating sperm transfer. Also, the males of this species have a few transverse striations in the dorsomedial part of notogaster (at level of porose areas A1 and A2). Further, we discuss all cases of sexual dimorphism in the superfamily Ceratozetoidea, and the possible function of this dimorphism.